(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ramlee A, Suhaimi H, Rasdi NW. 2021. Diversity and abundance of plankton in different habitat zonation of Papan River, Lake Kenyir, Malaysia. Biodiversitas 23: 212-221. Lake Kenyir is the largest artificial lake in Malaysia, yet there is limited information regarding the lake’s ecology. This study aimed to determine the diversity and abundance of phytoplankton and zooplankton in various habitat ecosystems along the Papan River, Lake Kenyir. Three distinct sampling points were chosen based on the diverse habitat conditions, namely sampling point A (high water current area), sampling point B (shallow and muddy area) and sampling point C (minimum water current area). Samples were collected horizontally using a 30µm plankton net with two distinct towing methods: boat and hand towing to specific areas. The result showed that all sampling points had low chlorophyll-a concentrations ranging between 10 and 20 g/ml, indicating that no algae bloom had occurred. Bacillariophyta were found to have the highest distribution of phytoplankton division in all of the stations (50.96%). The other division discovered was Chlorophyta (29.62%), followed by Charophyta (19.43%). Additionally, 140 individual zooplankton species were discovered across all sampling locations. The phylum Rotifera is the most dominant in terms of species distribution (60.00 %), followed by Arthropoda (31.43%), Ciliophora (7.14%), and Rhizopoda (0.71%). The Shannon diversity index, evenness, and species richness measurements at sampling point A, B, and C revealed a range of index values due to variation in plankton species due to interaction and habitat conditions. The variation in planktonic abundance in the Papan River was attributed to their habitat preferences due to the freshwater lake’s ecosystem’s different zones and conditions.